Phytoremediation of heavy metals contaminated soil using plant growth promoting rhizobacteria (PGPR): A current perspective - Hansda, Arti; Kumar, Vipin; Anshumali, Anshumali; Usmani, Zeba (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Increase in industrial, agricultural practices and several anthropogenic activities add a significant amount of heavy metals in soil and water. Heavy metals accumulate in the environment due to their non biodegradable nature and subsequently contaminate the food chain. Presence of these metals beyond the threshold limit poses a serious threat to the environment and human health. To overcome these problems, bioremediation has been getting attention because of its low cost, efficient and eco-friendly nature. Phytoremediation is a promising approach for removal of contaminants from the environment by the use of hyperaccumulator plants. But using plants alone for remediation faces many limitations owing to the heavy metal toxicity. This heavy metal toxicity could be conquered by exploring the association of plant growth promoting rhizobacteria (PGPR) with plants. This association would improve plant growth by facilitating sequestration of toxic heavy metals. Plant growth-promoting rhizobacteria are involved in plant growth promotion and development by colonizing the root or preventing plant diseases via production and secretion of various regulatory chemicals. Metal uptake mechanisms involve special proteins namely metallo-proteins or metal-binding proteins and peptides. This study deals with the role of PGPR in plant growth promotion and acceleration of phytoremediation as well as removal of toxic metals. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>